Re-investigation and RNA sequencing-based identification of genes with placenta-specific imprinted expression - Okae, Hiroaki; Hiura, Hitoshi; Nishida, Yuichiro; Funayama, Ryo; Tanaka, Satoshi; Chiba, Hatsune; Yaegashi, Nobuo; Nakayama, Keiko; Sasaki, Hiroyuki; Arima, Takahiro (Human molecular genetics, 2012)
Within the vertebrate groups, only mammals are subject to a specialized epigenetic process termed genomic imprinting in which genes are preferentially expressed from one parental allele. Imprinted expression has been reported for >100 mouse genes and, for approximately one-quarter of these genes, the imprinted expression is specific to the placenta (or extraembryonic tissues). This seemingly placenta-specific imprinted expression has garnered much attention, as has the apparent lack of conserved imprinting between the human and mouse placenta. In this study, we used a novel approach to re-investigate the placenta-specific expression using embryo transfer and trophoblast stem cells. We analyzed 20 genes previously reported to show maternal allele-specific expression in the placenta, and only 8 genes were confirmed to be imprinted. Other genes were likely to be falsely identified as imprinted due to their relatively high expression in contaminating maternal cells. Next, we performed a genome-wide transcriptome assay and identified 133 and 955 candidate imprinted genes with paternal allele- and maternal allele-specific expression. Of those we analyzed in detail, 1/6 (Gab1) of the candidates for paternal allele-specific expression and only 1/269 (Ano1) candidates for maternal allele-specific expression were authentically imprinted genes. Imprinting of Ano1 and Gab1 was specific to the placenta and neither gene displayed allele-specific promoter DNA methylation. Imprinting of ANO1, but not GAB1, was conserved in the human placenta. Our findings impose a considerable revision of the current views of placental imprinting.